Circular RNAs and their emerging roles in muscular immune-related diseases - Urzi, Felicita; Srpčič, Anja; Lakota, Katja (Frontiers in Immunology, 2025)
Circular RNAs (circRNAs) have recently emerged as a highly stable and versatile class of non-coding RNAs that play critical roles in gene regulation, yet their involvement in immune-mediated muscle disorders remains largely underexplored. This review synthesizes how circRNAs influence key processes in both skeletal muscle and immune cells, from myogenesis, regeneration, and muscle stem cell function to inflammatory signaling and muscle wasting. Our aim was to identify circRNA insights across muscle immune-mediated diseases. However, we found no idiopathic inflammatory myopathy-focused circRNA studies, only a limited body of work in Duchenne muscular dystrophy, and predominantly peripheral blood mononuclear cell-based evidence in myasthenia gravis. These gaps highlight clear priorities: subtype-resolved circRNA atlases for idiopathic inflammatory myopathy; paired muscle–biofluid and cell-type–resolved profiling (including infiltrating immune populations); rigorous in vivo functional validation beyond correlative expression; fuller mechanistic delineation beyond miRNA competition (e.g., RNA binding protein interactions, translation, epigenetic regulation); and longitudinal cohorts linking circRNA dynamics to disease activity and treatment response. We particularly noted lack of in-depth studies addressing the interplay between muscle and immune cells in these conditions. Furthermore, we examine pioneering efforts to engineer circRNAs as therapeutic agents, capable of either neutralizing pathogenic pathways that drive muscle atrophy or restoring dystrophin expression in genetic disease models. Finally, we outline future directions for circRNA profiling in patient tissues and biofluids, rigorous functional validation in vivo, and the development of circRNA-based diagnostics. This positions circRNAs at the forefront of next-generation strategies for understanding and combating immune-related muscular disorders.